2022
DOI: 10.3389/fphar.2022.966218
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic effect of YangshenDingzhi granules: Integrated network pharmacology and hippocampal metabolomics

Abstract: Anxiety disorder is one of the most common mental diseases. It is mainly characterized by a sudden, recurring but indescribable panic, fear, tension and/or anxiety. Yangshendingzhi granules (YSDZ) are widely used in the treatment of anxiety disorders, but its active ingredients and underlying mechanisms are not yet clear. This study integrates network pharmacology and metabolomics to investigate the potential mechanism of action of YSDZ in a rat model of anxiety. First, potential active ingredients and targets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…41 , 42 Studies have indicated that inflammatory marker levels are elevated in viral pneumonia, and YSDZ reduces the expression of TNF‐α, and IL‐1β inflammatory factors. 6 , 43 Thus, YSDZ could play a major role in the treatment of viral pneumonia by regulating the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…41 , 42 Studies have indicated that inflammatory marker levels are elevated in viral pneumonia, and YSDZ reduces the expression of TNF‐α, and IL‐1β inflammatory factors. 6 , 43 Thus, YSDZ could play a major role in the treatment of viral pneumonia by regulating the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…It has also demonstrated efficacy in preventing and treating respiratory diseases due to its heat-clearing, detoxifying, phlegm-dissolving, and cough-relieving properties. [6][7][8] The formulation utilizes specific herbs to replenish and promote the circulation of qi (vital energy) and blood, stabilize the spirit, expel wind, relieve external heat, dissolve phlegm, and tranquilize the spirit. YSDZ has demonstrated significant clinical efficacy in preventing and treating SARS-CoV-2 infection and was utilized in Tanzania's epidemic in 2020, marking a significant milestone in the international application of TCM against COVID-19.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vanquish ultra-high performance liquid chromatograph (UHPLC) (Thermo Fisher Scientific, USA) was used in this study. 22 Using Waters ACQUITY UPLC BEH Amide liquid chromatography column (2.1 mm × 50 mm, 1.7 μm; Milford, MA, USA), the target compounds were divided. In liquid chromatography, the aqueous phase (Phase A) consists of 25 mmol/L ammonium acetate and 25 mmol/L ammonia water, while the organic phase (Phase B) is composed of acetonitrile.…”
Section: Methodsmentioning
confidence: 99%